Study on the Application of MIKE Model to Assess the Effect of Climate Changes-Sea Level Rise on the Salinity Intrusion in the Estuaries in Vu Gia-Thu Bon River Basin, Vietnam - Nguyen, Ngoc Tue; Nguyen, Thu Ha; Nghiem, Thi Thuong; Pham, Van Tien; Ho, Huu Loc; Hoang, Van Dai (Old Journal, 2018)
In recent years, salinity intrusion is a major challenge for provinces in the central of Vietnam in general and Vu Gia Thu Bon river basin in particular under climate change sea level rise scenarios. In this paper, MIKE-NAM and MIKE 11 are used to simulate the salinity intrusion process during dry season by using RCP4.5 scenarios for Vietnam introduced by the Ministry of Natural Resources and Environment of Vietnam (2016) for 3 periods of 2016-2035, 2046-2065 and 2080-2099. In the base period 1986-2005, the results show that the distance of 1% and 4% salinity intrusion is reported at Vu Gia Rivers of 16.2km and 12.5km, 20.9km and 17.4km at Thu Bon River, respectively. According to the scenario RCP4.5, the distance of salinity intrusion extends into the inland about 4,2-5km compared to the base scenario by the end of the 21st century.